The Role of Tiktok in Shaping Aceh’s Destination Image and Its Implications for Local Community Development - Mawaddah, Mawaddah; Erfendy, Ulfa (Islamic Management and Empowerment Journal, 2026)
This study explores the role of TikTok in shaping Aceh’s destination image and its implications for local community development. Using qualitative content analysis, 3,960 comments from the three most-engaged Aceh tourism videos on TikTok were examined. The findings show that destination image was the most dominant theme, highlighting the influence of visual attractiveness, natural scenery, and aesthetic representations in shaping perceptions of Aceh. Travel interest also emerged as a significant theme, indicating that TikTok exposure can encourage visitation intentions. Public sentiment was relatively balanced, with positive comments emphasizing Aceh’s cultural uniqueness and Islamic identity, while negative comments mainly concerned the implementation of Sharia law for visitors. Islamic and halal values contributed to destination image formation but were not the primary drivers. The study further suggests that increased tourism visibility through TikTok can support local community development by creating opportunities for tourism businesses, cultural promotion, and community-based tourism initiatives. These findings underline TikTok’s role as an effective tool for digital destination branding and sustainable tourism development.